The development and prediction of athletic performance in freestyle swimming - Stanula, A.; Maszczyk, A.; Roczniok, R.; Pietraszewski, P.; Ostrowski, A.; Zajac, A.; Strzala, M. (Journal of Human Kinetics, 2012)
This paper analyses the dynamics of changes between the performances of elite freestyle swimmers recorded at particular Olympic Games. It also uses a set of chronologically ordered results to predict probable times of swimmers at the 2012 Olympic Games in London. The analysis of past performances of freestyle swimmers and their prediction have revealed a number of interesting tendencies within separately examined results of men and women. Women's results improve more dynamically compared with men's. Moreover, the difference between women's and men's results is smaller, the longer the swimming distance. As both male and female athletes tend to compete more and more vigorously within their groups, the gap between the gold medallist and the last finisher in the final is constantly decreasing, which provides significant evidence that this sport discipline continues to develop.